Solitary fibrous tumour of caecum wall: an unlikely cause of low gastrointestinal haemorrhage - Santos, Mariana Nogueira (BMJ Case Rep, 2018)
Solitary fibrous tumour (SFT), previously denominated as haemangiopericytoma, is a rare, spindle cell neoplasm that was first described in the thoracic pleura. It is now known that this tumour may develop from almost any anatomic location. We report a case of SFT, in a 65-year-old man, which was located in the muscularis propria layer of the caecum with involvement of the serosa and the ileocecal appendix, location never described in the literature, and with an uncommon clinical presentation of hematochezia. A radical right hemicolectomy was performed, and the patient was asymptomatic without evidence of metastasis or relapse after 6 months of follow-up.